The Effects of Person-Job Fit on Employee Engagement Among Lecturers in Higher Education Institutions: Is There a Difference Between Lecturers in Public and Private Higher Education Institutions? - Sulistiowati, Sulistiowati; Komari, Nurul; Dhamayanti, Endang (International Review of Management and Marketing, 2018)
The suitability between task/job characteristics and individual ability to perform tasks will strengthen the human resource engagement to their work. At higher education institutions, the person-job fit plays an important role. This study aims to examine the effects of person-job fit on employee engagement among lectures at higher education institutions and to find out whether there are significant differences regarding person-job fit and employee engagement between public higher education lecturers and private higher education lecturers. The populations in this study were all lecturers of higher education institutions in the Province of West Kalimantan, Indonesia, amounting to 2,686 people. The number of research samples was 160, with the composition of 80 public higher education lecturers and 80 private higher education lecturers. The hypothesis test used was linear regression and t-test. Based on the results of regression test, it can be concluded that there is an effect of person-job fit on employee engagement. From the result of T test, it can be concluded that there are significant differences in person-job fit and employee engagement between public higher education lecturers and private higher education lecturers. Keywords: Person-job fit, employee engagement, higher education JEL Classification: I2